PENGEMBANGAN BAHAN AJAR MATEMATIKA DENGAN PENDEKATAN SCIENTIFIC UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMA NEGERI 1 BANDAR PULAU - Dita Puja Lestari (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
The purpose of this research is to examine: (1) How the validity ofteaching subject which developed by scientific approaching that used toimproves the sability critical thinking mathematically of student, (2) Howthe effectiveness of teaching subject which this developed by scientificapproaching that used to improved the abiliity critical thinkingmathematically of student and (3) How the improvement of the abilitycritical thinking mathematically of student by using teaching subjectwhich developed by approaaching scientific. Teacing subject is A book,RPP and LKS instrument test result. Population in this research is all ofstudent class X SMA Negeri 1 Bandar Pulau which is totally there are141 studdents. Taking samples from 2 class room which totally there are71 students. This research equal to research improvement use exampleThiagarajan, Semmel and Semmel are modified by 4D model. There are 4step for development processing: define, design, develop anddisseminate. Data analisist result have gotten shoeing that teachingsubject with approaching scientific at trigonometri clas X SMA Negeri 1Bandar Pulau are valid and effctive.